Fast Growth of Thin MAPbI3 Crystal Wafers on Aqueous Solution Surface for Efficient Lateral‐Structure Perovskite Solar Cells. (23rd January 2019) - Liu, Ye; Dong, Qingfeng; Fang, Yanjun; Lin, Yuze; Deng, Yehao; Huang, Jinsong
Abstract: Solar‐grade single or multiple crystalline wafers are needed in large quantities in the solar cell industry, and are generally formed by a top‐down process from crystal ingots, which causes a significant waste of materials and energy during slicing, polishing, and other processing. Here, a bottom‐up technique that allows the growth of wafer‐size hybrid perovskite multiple crystals directly from aqueous solution is reported. Single‐crystalline hybrid perovskite wafers with centimeter size are grown at the top surface of a perovskite precursor solution. As well as saving raw materials, this method provides unprecedented advantages such as easily tunable thickness and rapid growth of the crystals. These crystalline wafers show high crystallinity, broader light absorption, and a long carrier recombination lifetime, comparable with those of bulk single crystals. Lateral‐structure perovskite solar cells made of these crystals demonstrate a record power conversion efficiency of 5.9%. Abstract : Here a method to grow wafer‐size thin halide perovskite multiple crystals on aqueous solution surface is reported. The efficiency of lateral‐structure solar cells based on the single‐crystalline perovskite wafer reaches 5.9%.